Keeping your Friends Close: British Foreign Policy and the Nordic Economic Community, 1968–1972. (5th April 2016) - BROAD, MATTHEW
Abstract: The Nordic Economic Community (Nordek) was a short-lived and ultimately unsuccessful attempt to strengthen cooperation between the four Nordic states. While the importance of the project to Britain has often been overlooked, this article suggests that Whitehall took considerable interest from the start. It demonstrates how, although officially neutral, London sought first to mitigate the effects of Nordek, then to undermine its establishment and, finally, in the wake of Nordek's collapse, to guard against its re-emergence. The aim throughout was to protect three central tenets of British foreign policy: EFTA unity in light of the second veto, Britain's own application for EEC membership and a cohesive Western Europe militarily integrated in NATO. However, the article highlights the absence of a coherent strategy towards tentative Nordic integration and the mixed success this brought, the interdependency of Anglo-Nordic relations in the pursuit and success of British foreign policy goals and the relative decline of the Britain's influence in the Nordic region.